MicroRNA‐binding proteins: specificity and function. (28th January 2017) - Zealy, Richard W.; Wrenn, Samuel P.; Davila, Sylvia; Min, Kyung‐Won; Yoon, Je‐Hyun
Abstract : microRNA (miRNA) and RNA‐binding proteins (RBPs) have been studied widely in post‐transcriptional gene regulation. Previous work has focused on defining how miRNA and RBPs modulate target mRNA decay and translation as well as investigating how they interplay each other. Emerging studies indicate that certain RBPs other than the AGO‐family proteins directly interact with mature miRNAs. These findings implicate competitive binding of RBPs to target miRNAs, sequestration of miRNAs from AGO, promotion of AGO binding to miRNAs, and transfer of miRNAs from RBPs to AGO. Recent work also indicates that AGO‐free cytoplasmic miRNAs establish complexes with novel miRNA‐binding proteins (miRBPs). This review covers the recent discovery of novel miRBPs, offering a new perspective on the miRNA‐mediated gene silencing mechanism. WIREs RNA 2017, 8:e1414. doi: 10.1002/wrna.1414 This article is categorized under: RNA Interactions with Proteins and Other Molecules > Protein–RNA Recognition RNA Interactions with Proteins and Other Molecules > Protein–RNA Interactions: Functional Implications Regulatory RNAs/RNAi/Riboswitches > Regulatory RNAs Abstract : miRNA‐binding proteins (miRBPs) cooperate or compete with AGO2 for miRNA binding in miRNA‐mediated gene silencing.